2014
DOI: 10.1073/pnas.1407756111
|View full text |Cite
|
Sign up to set email alerts
|

Context effects produced by question orders reveal quantum nature of human judgments

Abstract: The hypothesis that human reasoning obeys the laws of quantum rather than classical probability has been used in recent years to explain a variety of seemingly "irrational" judgment and decisionmaking findings. This article provides independent evidence for this hypothesis based on an a priori prediction, called the quantum question (QQ) equality, concerning the effect of asking attitude questions successively in different orders. We empirically evaluated the predicted QQ equality using 70 national representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
311
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(320 citation statements)
references
References 24 publications
7
311
0
2
Order By: Relevance
“…This enables a direct test of the quantum-like account of the conjunction fallacy, that we apply to our collected experimental data. In addition, it has been shown that any quantum-like model of the kind involved in the account of the conjunction fallacy must make an empirical prediction called the "QQ equality" Wang et al 2014). We thus test whether the QQ equality is verified.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…This enables a direct test of the quantum-like account of the conjunction fallacy, that we apply to our collected experimental data. In addition, it has been shown that any quantum-like model of the kind involved in the account of the conjunction fallacy must make an empirical prediction called the "QQ equality" Wang et al 2014). We thus test whether the QQ equality is verified.…”
Section: Introductionmentioning
confidence: 94%
“…This comes from the projection postulate that modifies the state of belief when an answer is given to a question. This order effect property of the quantum-like models is well known, and it has actually been used to provide a quantum-like account of order effect (see for example Conte et al 2009;Busemeyer et al 2009Busemeyer et al , 2011Atmanspacher and Römer 2012;Pothos and Busemeyer 2013;Wang and Busemeyer 2013;Wang et al 2014;Boyer-Kassem et al 2016)-thus, the same models are at the basis of the account of order effect and of the conjunction fallacy. Fig.…”
Section: Order Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…We know that it is not uncommon for decision makers to employ contextual representations, as demonstrated by the various QPT models for probabilistic fallacies (note, it will not be possible to explain all probabilistic fallacies in quantum terms; cf. Wang et al, 2014). What would be the frequency of such situations?…”
Section: Implications For Real World Decision Makingmentioning
confidence: 99%